2016
DOI: 10.1038/srep37585
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lysophosphatidic acid receptors 1 and 3 attenuates atherosclerosis development in LDL-receptor deficient mice

Abstract: Lysophosphatidic acid (LPA) is a natural lysophospholipid present at high concentrations within lipid-rich atherosclerotic plaques. Upon local accumulation in the damaged vessels, LPA can act as a potent activator for various types of immune cells through its specific membrane receptors LPA1/3. LPA elicits chemotactic, pro-inflammatory and apoptotic effects that lead to atherosclerotic plaque progression. In this study we aimed to inhibit LPA signaling by means of LPA1/3 antagonism using the small molecule Ki1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
(64 reference statements)
3
17
1
Order By: Relevance
“…However, modulations of a specific GPCR have limits, as diseases are commonly driven by the simultaneous involvement of multiple receptors. Our study identifies Gα13 as the signaling node that regulates metabolic adaptation to extracellular stimuli, as supported by our findings that Gα13 levels in skeletal muscle were repressed by exercise, but increased under metabolic disease conditions, and that the genetic KO facilitated the reprogramming vides metabolic benefits such as the attenuation of diet-induced obesity and atherosclerosis development in mice (51,52). Inhibitors selectively targeting Rock2 or Ser243 phosphorylation of NFATc1 can also be attractive therapeutic candidates for metabolic diseases, as has already been observed in part with a nonselective Rock inhibitor (53).…”
Section: Discussionsupporting
confidence: 62%
“…However, modulations of a specific GPCR have limits, as diseases are commonly driven by the simultaneous involvement of multiple receptors. Our study identifies Gα13 as the signaling node that regulates metabolic adaptation to extracellular stimuli, as supported by our findings that Gα13 levels in skeletal muscle were repressed by exercise, but increased under metabolic disease conditions, and that the genetic KO facilitated the reprogramming vides metabolic benefits such as the attenuation of diet-induced obesity and atherosclerosis development in mice (51,52). Inhibitors selectively targeting Rock2 or Ser243 phosphorylation of NFATc1 can also be attractive therapeutic candidates for metabolic diseases, as has already been observed in part with a nonselective Rock inhibitor (53).…”
Section: Discussionsupporting
confidence: 62%
“…Macrophage positive area in the plaque was determined by using MOMA2 staining. [ 41 ] Macrophage positive area was calculated as the area positive for the MOMA2 staining divided by the total plaque area for the three largest consecutive sections. Collagen content in the plaques was measured by using Sirius Red staining.…”
Section: Methodsmentioning
confidence: 99%
“…These findings indicated that LPA may contribute to the pathological process of atherosclerosis. In addition, Kritikou et al ( 14 ) suggested that the inhibition of LPA receptors may reduce the size of atherosclerotic plaques. Since LPA serves such a critical role in atherosclerosis, it may be considered a promising therapeutic target for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LPA is associated with various vessel wall cell activities, and contributes to vasculogenesis, angiogenesis and vascular remodeling ( 7 , 10 12 ). Indirect evidence that blockade of LPA receptors reduces neointimal hyperplasia has demonstrated that LPA may be involved in neointimal formation following vascular injury and LPA receptor blockade relieves atherosclerotic development ( 13 , 14 ); however, the effects of LPA on neointimal formation remain unclear.…”
Section: Introductionmentioning
confidence: 99%